2020
DOI: 10.3390/mi11080708
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Investigation of Near-Infrared Fabry–Pérot Microcavity Graphene/Silicon Schottky Photodetectors Based on Double Silicon on Insulator Substrates

Abstract: In this work a new concept of silicon resonant cavity enhanced photodetector working at 1550 nm has been theoretically investigated. The absorption mechanism is based on the internal photoemission effect through a graphene/silicon Schottky junction incorporated into a silicon-based Fabry–Pérot optical microcavity whose input mirror is constituted by a double silicon-on-insulator substrate. As output mirror we have investigated two options: a distributed Bragg reflector constituted by some periods of silicon ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…Further, in this work the bandwidth and the noise of the device were discussed. In addition, a similar device taking advantage of a double silicon on insulator substrate working as a high-reflectivity mirror has been recently proposed and theoretically discussed [43].…”
Section: Schottky Silicon Photodetectors Based On 2d Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, in this work the bandwidth and the noise of the device were discussed. In addition, a similar device taking advantage of a double silicon on insulator substrate working as a high-reflectivity mirror has been recently proposed and theoretically discussed [43].…”
Section: Schottky Silicon Photodetectors Based On 2d Materialsmentioning
confidence: 99%
“…Further, in this work the bandwidth and the noise of the device were discussed. In addition, a similar device taking advantage of a double silicon on insulator substrate working as a high-reflectivity mirror has been recently proposed and theoretically discussed [43]. In 2016 Cheng et al [44] demonstrated graphene short-wave NIR PDs with a very high responsivity of 83A/W at 1.55μm thanks to the combination of two different mechanisms that allow the improvement of the performances of their devices.…”
Section: Schottky Silicon Photodetectors Based On 2d Materialsmentioning
confidence: 99%
“…In previous work, we proposed to realize a resonant-cavity-enhanced (RCE) photodetector based on a hydrogenated amorphous silicon (a-Si:H)/Gr/crystalline silicon (c-Si) microcavity built on top of a double silicon-on-insulator (DSOI) substrate, manufactured for high reflectivity at 1550 nm and working as an input mirror [ 29 ]. In this work, we showed that the employment of a distributed Bragg reflector (DBR), constituted by five periods of silicon nitride (Si 3 N 4 )/a-Si:H, as an output mirror was the best option to optimize the PD efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, graphene/Si Schottky PDs have shown higher efficiencies with respect to the metallic counterpart and, even if the physical mechanism behind this enhancement is still under debate, it seems related to the increased emission probability due to the two-dimensionality of the material [16][17][18]. Although graphene is characterized by a low optical absorption (2.3%) many approaches based on resonant-cavity-enhanced (RCE) configurations [19,20], plasmonic structures [21], waveguiding structures [22], and quantum dots [23] have been proposed to overcome this drawback. At present, graphene/Si PDs [18,22,24] show superior performance to the corresponding metallic PDs, representing the most promising solution to realize low-cost Si PDs operating in the NIR regime.…”
Section: Introductionmentioning
confidence: 99%